Mapping the Landscape: Indonesian Fermented Foods, Probiotics, and Cardiovascular Disease Prevention - A Bibliometric and Scoping Review - Purbosari, Para Mitta; Rahardjo, Sentot Budi; Widoretno, Sri; Sarwanto, S (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Cardiovascular disease (CVD) constitutes a significant health burden in Indonesia, accounting for approximately one-third of all deaths. Hypercholesterolemia and dyslipidemia are established primary risk factors for CVD. This mini-review synthesizes current knowledge on CVD, the characteristics of probiotic bacteria, and the potential of Indonesian fermented foods to mitigate CVD risk. Indonesia boasts a rich and diverse array of traditional fermented foods, including tape, tempeh, dadih, sayur asin, tempoyak, and growol. Notably, many of these foods harbor diverse probiotic microorganisms, such as Lactobacillus, Bifidobacterium, Lactococcus, Streptococcus, Enterococcus, Weissella, Pediococcus, Rhizopus, Penicillium, and Saccharomyces. Various studies have explored the beneficial effects of probiotics, with hypocholesterolemic and hypolipidemic effects increasing in recent years. Consistent consumption of probiotics has demonstrated the potential to reduce total serum cholesterol, low-density lipoprotein cholesterol, liver cholesterol, and triglycerides, while concurrently elevating high-density lipoprotein cholesterol. The impact of probiotics on lipid profiles is influenced by many factors, such as the specific probiotic strain, dosage, and the individual's dietary habits and overall health status. This review highlighted the promising role of probiotics derived from Indonesian fermented foods as a complementary strategy in preventing cardiovascular disease.